Equipment utilization in chronic total occlusion percutaneous coronary interventions: Insights from the PROGRESS‐CTO registry. Issue 4 (29th June 2020) - Nikolakopoulos, Ilias; Choi, James W.; Alaswad, Khaldoon; Khatri, Jaikirshan J.; Krestyaninov, Oleg; Khelimskii, Dmitrii; Yeh, Robert W.; Jaffer, Farouc A.; Toma, Catalin; Patel, Mitul; Mahmud, Ehtisham; Lembo, Nicholas J.; et al.
Abstract: Background: We examined guidewire and microcatheter utilization during chronic total occlusion (CTO) percutaneous coronary intervention (PCI). Methods: We examined device utilization in 2, 968 CTO PCIs performed in 2, 936 patients at 19 US and two international center between January 2016 and January 2019. Results: The median number of antegrade guidewires used per case declined (5 in 2016 vs 3 in 2019) and was higher in higher complexity lesions (2 in J‐CTO 0 vs. 8 in J‐CTO 4 or 5 score). In antegrade‐only procedures, the most frequently used guidewires were the Pilot 200 (Abbott Vascular, 37%), Fielder XT (Asahi Intecc, 25%) and Gaia third (Asahi Intecc, 18%), while the most commonly used microcatheters were the Turnpike Spiral (Vascular Solutions, 18%) and Turnpike (Vascular Solutions, 16%). Compared with 2012–2015, during 2016–2019 use of novel equipment such as the Gaia guidewires and the Turnpike microcatheters led to decreased use of Confianza Pro 12 (Asahi Intecc) wire and Corsair (Asahi Intecc) family of microcatheters. In retrograde cases, the guidewires most commonly used were the Sion (44%), Pilot 200 (27%) and Fielder FC (26%), while the Corsair/Corsair Pro, Turnpike LP (Vascular Solutions) and Caravel (Asahi Intecc) were the most frequently used microcatheters for collateral crossing (29%, 26% and 22%, respectively). Conclusions: The most commonly used guidewires during CTO PCI are polymer‐jacketed guidewires and the most commonly used microcatheters are torquable microcatheters.